Valorization of Trash Fish Through Drying Innovations: Nutrient Stability of Protein, Calcium, and Phosphorus - Subakir Salnus; Zulfian Armah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Trash fish, often regarded as low-value bycatch, actually holds significant potential as a source of protein and essential minerals such as calcium and phosphorus. This study aims to evaluate the effect of different drying methods—oven drying at varying temperatures (40°C, 60°C, 80°C, and 100°C) and sun drying on the protein, calcium, and phosphorus content of trash fish. Laboratory analyses were conducted using the Kjeldahl method for protein determination and atomic absorption spectrophotometry (AAS) for calcium and phosphorus content. The results revealed that increasing oven drying temperatures significantly reduced protein levels, while sun drying maintained a protein content close to the optimal range. In contrast, calcium and phosphorus levels showed no significant differences across drying methods. Therefore, low-temperature oven drying or sun drying is recommended to preserve the nutritional quality of trash fish effectively.